Loneliness and Telomere Length: Immune and Parasympathetic Function in Associations With Accelerated Aging - Wilson, Stephanie J (Ann Behav Med, 2018)
BACKGROUND: Lonely people’s heightened risks for chronic health conditions and early mortality may emerge in part through cellular aging. Lonelier people have more severe sympathetic responses to acute stress, increasing their risk for herpesvirus reactivation, a possible path to shorter telomeres. Parasympathetic function may modulate this risk. PURPOSE: The current study aimed to examine the associations among loneliness, herpesvirus reactivation, and telomere length, with parasympathetic activity as a moderator, in healthy middle-aged and older adults. METHODS: A sample of 113 healthy men and women of ages 40–85 provided blood samples that were assayed for telomere length, as well as the latent herpesviruses cytomegalovirus (CMV) and Epstein-Barr virus (EBV). They also provided heart rate variability (HRV), a measure of parasympathetic activity, and reported on their feelings of loneliness. RESULTS: Lonelier people with lower HRV (i.e., lower parasympathetic activity) had greater CMV reactivation and shorter telomeres compared with their less lonely counterparts, above and beyond demographics, health behaviors, resting heart rate, and social network size. However, loneliness was not associated with viral reactivation or telomere length among those with higher HRV. In turn, greater CMV and EBV reactivation was associated with shorter telomeres. CONCLUSIONS: Taken together, these data implicate parasympathetic function in novel links between loneliness and accelerated cellular aging.